Acceptance towards goods and services tax (GST) and sales and services tax (SST) among local business communities in Cheras area: A comparison study - Khoo, Khim Hoong; Yong, Chin Yee (2018)
This research aim to study the factors which include awareness, understanding and attitude that influence the level of acceptance towards Goods and Services Tax (GST) as well as Sales and Services Tax (SST) among business communities in Cheras area. Throughout this study, non-probability sampling technique was applied to collect the data. In order to ensure the research data are reliable, primary data (questionnaire) and secondary data were adopted in this study. A total of 3 analysis comprises of descriptive analysis, reliability test and inferential analysis (Multiple Linear Regression) was obtained through the Statistical Package for Social Science (SPSS) version 23.0. The result obtained from the analysis has been tabulated and discussed in details in the Chapter 4 of this study. In the end of the study, the limitations encountered by researchers and recommendations were suggested for further improvement has been discussed in chapter 5. In the end of this research, it has shown that understanding towards GST and attitude towards SST has significant effect toward the level of acceptance towards GST and SST respectively. Whereas the awareness and attitude toward GST, awareness and understanding towards SST have insignificant relationship with acceptance level towards GST and SST respectively. In conclusion, it hoped that this research finding able to provide some useful information for Malaysia’s tax authority in order to improve the implementing tax system in Malaysia which can help to maintain country economic stability.